Analisis Penggunaan E-Commerce Shopee terhadap Perilaku Konsumtif pada Generasi Z (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi Universitas Nadhlatul Ulama Kalimantan Barat) - Dani, Rama; Firayanti, Yuni; Wulansari, Fidia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The purpose of this study is to determine the impact of the use of e-commerce shopee in influencing consumer behavior on Generation Z students. The research method used is qualitative with case studies. Data collection techniques in this study are through interviews, observations, and documentation. The results of this study indicate that the presence of various e-commerce platforms in Indonesia greatly influences changes in people's behavior patterns, especially Generation Z students in shopping online. The consumer behavior of Generation Z students in management study programs is caused by various factors, namely affordable prices, promos and discounts, ease of use, product variety, speed of delivery, ease of returning goods, and the influence of influencers and social media. The impact of e-commerce shopee impacts students' online shopping habits. This study concludes that the presence of various e-commerce platforms on the internet has an impact on and changes in society, especially students, in online shopping in the current digital era.